The potency of Mentega Cassava (Manihot esculenta) Variety Peels Waste as Raw Material for Bioethanol by Enzymatic Hydrolisis - Essa Annisa Syadiah; Fitrah Adelina; S Sudarmin; Fitrianti Handayani; Juniaty Arruan Bulawan (EDUFORTECH, 2022)
Cassava peel waste can be used as an energy source in the form of bioethanol. The need for bioethanol is increasing both asalternative energy to replace fuel oil (BBM). Ethanol (C2H5OH) is the result of conversion from the sugar fermentation process using the help of microorganisms. This study aims to determine the levels of bioethanol produced from cassava peel obtained from Ibun sub-district, Bandung Regency through enzymatic treatment. The research procedure started from the pretreatment of cassava peel waste as a substrate, enzymatic hydrolysis, and fermentation. Enzymatic hydrolysis using Trichoderma viride isolates with 3 variations in inoculum concentrations of 10%, 15%, and 20%. As for the fermentation process using Saccharomyces cerevisiae isolates. The highest reducing sugar of 21.28 mg/L was produced by treatment with hydrolysis time of 60 hours and inoculum concentration of 10%. The highest bioethanol content was 4.9 mg/L with a fermentation time of 96 hours.